Empirical Analysis on Human Resource Management and ICT Use for Product Innovation among Firms in ASEAN Economies - Hiroki Idota; Yasushi Ueki; Hidenori Shigeno; Teruyuki Bunno; Masatsugu Tsuji (International Telecommunications Society (ITS), 2016)
To achieve successful innovation, firms in ASEAN countries have to elevate their innovation capability including human resources, business structure of firms, technologies including ICT use by collaborating with outside organizations such as MNCs (Multi-national companies) and university/public research institutes. These outside organizations are termed as external linkages. Based on authors'survey data of five ASEAN economies such as Vietnam, Indonesia, the Philippines, Thailand, and Laos from 2014 to 2015, this paper examines how internal innovation capability such as human resource management (HRM), organizational learning and ICT use enhance product innovation. These factors are used as latent variables in analysis and consist of the following variables:(i) HRM such as recruitment, job training and rewards and 5S; (ii) organizational learning including QC and cross-functional teams;(iii) ICT use such as B2B, B2C, EDI, SCM, ERP, CAD/CAM, groupware, SNS; and (iv) external linkages. This study employs SEM (Structural equation modeling) to analyze the causal relationships not only among the above four latent variables but also between these and innovation.The six hypotheses were postulated. Estimation results demonstrate that organization learning and ICT use enhance product innovation, and particularly, human resource management enhances organization learning.
Keywords: O32; O31; O19; 330; ICT use; human resource management; external linkages; cross-functional teams; QC; SEM